Asthma and the Coronavirus Disease 2019 Pandemic - Morais-Almeida, Mário (2020)
Even though respiratory viruses are one of the most common triggers for asthma exacerbations, not all of these viruses affect patients equally. There is no strong evidence supporting that patients with asthma have a higher risk of becoming seriously ill from coronavirus disease 2019 (CO-VID-19), although recent reports from the USA and the UK suggest that asthma is much more common in children and adults with mild to severe COVID-19 than has previously been reported in Asia and in Europe. As in previous severe acute respiratory syndrome (SARS) outbreaks, patients with asthma, especially children, appear to be less susceptible to the coronavirus with a low rate of asthma exacerbations. A different expression of viral receptors and T2 inflammation can be responsible for different outcomes. Future studies focused on asthma and on other allergic disorders are needed to provide a greater understanding of the impact of underlying asthma and allergic inflammation on COVID-19 susceptibility and disease severity. However, for the moment, it is crucial that asthmatic patients maintain their controller medication, from inhaled corticosteroids to biologics, without making any dose adjustments on their own or stopping the medication. New data are emerging daily, rapidly updating our understanding of this novel coronavirus.